Pengurusan Penyelenggaraan Kemudahan Infrastruktur di Kawasan Ekopelancongan Sungai Muar, Johor - Shafii, Haryati; Md Jamil, Siti Nur Isma Zura Zulika; Mat Yassin, Azlina; Masram, Haidaliza; Omar, Roshartini (Research in Management of Technology and Business, 2021)
The maintenance management of tourism infrastructure development plays an important role in ensuring the comfort of visitors. However, the issue raised in this study is that the weakness of the maintenance management of infrastructure facilities can affect the discomfort to visitors while using them. The objective of this study is to identify the types of ecotourism infrastructure development maintenance management in Sungai Muar and propose methods of ecotourism infrastructure development maintenance management in Sungai Muar. The location of this study is around the Muar River area which has the potential to be an ecotourism area. This study uses qualitative methods, namely semi -structured interview method and observation method. The number of respondents involved in this study is three people, namely a head of engineering department and two assistant engineers from the Muar Municipal Council (MPM). The results of the study found that the interviews with R2 and R3 stated that the type of maintenance management in infrastructure development in the surrounding area is periodic and non -periodic which includes cleaning and inspection. The results of the interviews also found that R1 and R2 stated that the maintenance unit and the fast unit act as the unit that manages all infrastructure development in the Sungai Muar area. R1, R2 and R3 state that the lifespan of the infrastructure that can be used after maintenance work is different depending on the level of use, two weeks after the expiration of the maintenance warranty and the type of damage (within two weeks). R1 and R2 also state that the division of maintenance management work is according to the type of infrastructure that is based on the units that have been set. n contrast to the view of R3 which states the division of maintenance work is according to the field of expertise. In conclusion, maintenance management is very important to ensure the quality of the infrastructure is always in good condition and to ensure the comfort of visitors.